2019
DOI: 10.1038/s41598-019-56635-0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct role of Sirtuin 1 (SIRT1) and Sirtuin 2 (SIRT2) in inhibiting cargo-loading and release of extracellular vesicles

Abstract: Exosomes, vehicles for intercellular communication, are formed intracellularly within multivesicular bodies (MVBs) and are released upon fusion with the plasma membrane. For their biogenesis, proper cargo loading to exosomes and vesicle traffic for extracellular release are required. Previously we showed that the L-type lectin, LMAN2, limits trans-Golgi Network (TGN)-to-endosomes traffic of GPRC5B, an exosome cargo protein, for exosome release. Here, we identified that the protein deacetylase sirtuin 2 (SIRT2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 27 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Interestingly, Sirt1 has been measured in circulation (30,39,41,72), although its precise origin and its relationship to tissue content have yet to be completely elucidated. A possibility is that Sirt1 is secreted as part of extracellular vesicles, which is not surprising considering that proteins packaged into these vesicles are part of the mechanisms of biogenesis, and Sirt1 has a critical role in exosome secretion and lysosome function (33)(34)(35)45). This hypothesis has been supported by previous experiments that demonstrated the presence of another sirtuin in exosomes from oligodendroglial cells (16).…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, Sirt1 has been measured in circulation (30,39,41,72), although its precise origin and its relationship to tissue content have yet to be completely elucidated. A possibility is that Sirt1 is secreted as part of extracellular vesicles, which is not surprising considering that proteins packaged into these vesicles are part of the mechanisms of biogenesis, and Sirt1 has a critical role in exosome secretion and lysosome function (33)(34)(35)45). This hypothesis has been supported by previous experiments that demonstrated the presence of another sirtuin in exosomes from oligodendroglial cells (16).…”
Section: Discussionmentioning
confidence: 75%
“…A recent study exhibits that inhibition of SIRT1 by caveolin-1 in senescent fibroblasts promotes the secretion of interleukin 6 (IL-6) and stimulates tumor growth [110]. The latest progress discovers that SIRT1 is responsible for the change of microenvironment by regulating the secretion of exosomes [111] (Fig. 4).…”
Section: Sirt1 and Tumor Microenvironmentmentioning
confidence: 99%
“…The latest progress discovers that SIRT1 is responsible for the change of microenvironment by regulating the secretion of exosomes 111 (Fig. 4 ).…”
Section: Sirt1 and Tumor Microenvironmentmentioning
confidence: 99%
“…Lee et al . showed that loss of SirT2 expression also increased the total number of EVs, albeit by a separate suggested mechanism than that of SirT1 [ 55 ]. Others have also reported an association between loss of SirT1 and increased EV/exosome release [ 56 ].…”
mentioning
confidence: 99%